Acetazolamide alleviates sequelae of hyperglycaemic intracerebral haemorrhage by suppressing astrocytic reactive oxygen species. (2nd September 2018) - Chiu, Cheng-Di; Chiu, You-Pen; Lin, Cheng-Li; Ji, Hui-Ru; Shen, Chiung-Chyi; Lee, Hsu-Tung; Chang, Chen
Abstract: Hyperglycaemia is associated with the poor outcome after intracerebral haemorrhage (ICH). Acetazolamide (AZA), a kind of carbonic anhydrogenase (CA) inhibitor, its effectiveness in ICH had been reported. However, the connections between AZA and ICH, especially in hyperglycaemia condition had never been defined. In this study, adult Sprague–Dawley rats were administered with vehicle or streptozotocin (STZ) to render them into normoglycaemic (NG) or hyperglycaemic (HG), respectively. Collagenase was then injected into the striatum. The NG or HG ICH rats treated with vehicle control or 5 mg/kg AZA (oral gavage) underwent haemorrhagic area assessments on the 1st, 4th, and 7th day after ICH. The coverage of pericytes was examined by immunohistochemistry. Reactive oxygen species (ROS) levels were assessed in mouse astrocyte cell line treated with vehicle or 20 μmol/L of AZA in culture media according to two different glucose concentrations. AZA reduced the haematoma size, improved neurobehavioral functions, suppressed astrocytic ROS production in vitro, and preserved cerebral pericytes coverage, which are even more remarkable in HG conditions. The present study indicates that AZA may alleviate some sequelae after ICH, especially in poorer prognostic HG rats through the suppression of astrocytic ROS production.